PRIMA 2019: Principles and Practice of Multi-Agent Systems : 22nd International Conference, Turin, Italy, October 28-31, 2019, Proceedings - Baldoni, Matteo; Dastani, Mehdi; Liao, Beishui; Sakurai, Yuko; Wenkstern, Rym Zalila (Lecture Notes in Artificial Intelligence, 2019)
This book constitutes the refereed proceedings of the 22nd International Conference on Principles and Practice of Multi-Agent Systems, PRIMA 2019, held in Turin, Italy, in October 2019. The 25 full papers presented and 25 short papers were carefully reviewed and selected from 112 submissions.  The papers presented at the PRIMA 2019 conference focus on the following topics: Logic and Reasoning, Engineering Multi-Agent Systems, Agent-Based Modeling and Simulation, Collaboration and Coordination, Economic Paradigms, Human-Agent Interaction, Decentralized Paradigms, and Application Domains for Multi-Agent Systems.